Comparing training methods to improve volunteer skills during therapeutic horseback riding: A randomized control trial. Issue 3 (17th March 2021) - St. Peter, Claire C.; Shuler, Natalie J.; Jones, Stephanie H.; Bradtke, Sarah; Hull, Sydney L.; Browning, Bethany; VanGilder, Stephanie; Petitto, Carol
Abstract : Although in‐vivo behavioral skills training (BST) is often effective, it may be too resource‐intensive for organizations that rely on volunteers. Alternatives to in‐vivo BST include video models or interactive computer training (ICT), but the utility of these procedures for training volunteers remains largely unknown. We used a randomized control trial to teach multiple skills to new volunteers at a therapeutic riding center. A total of 60 volunteers were assigned to one of three groups using block randomization. Depending on group assignment, volunteers received instructions and modeling through in‐vivo interactions, a video model, or ICT. All volunteers completed in‐vivo role plays with feedback. Skills were measured by unblinded observers during role plays. There were no statistically significant differences in accuracy of role‐play performance between volunteers in the in‐vivo BST and ICT groups, but both outperformed the video‐model group. The ICT and video model required statistically significantly less time from a live instructor than did in‐vivo training. Thus, although in‐vivo BST remains best practice, ICT may be a viable alternative when training resources are limited.